Post-traumatic stress symptoms in parents of adolescents hospitalized with Anorexia nervosa. Issue 3 (4th May 2023) - Timko, C. Alix; Dennis, Nicholas J.; Mears, Connor; Rodriguez, Daniel; Fitzpatrick, Kathleen Kara; Peebles, Rebecka
ABSTRACT: The current study was a planned secondary analysis to examine post-traumatic stress symptoms (PTSS) in parents of youth hospitalized for medical stabilization due to anorexia nervosa (AN). Questionnaires were administered to 47 parents (34 mothers, 13 fathers; 10 parental dyads) after admission; follow-up occurred at discharge and 4 weeks, 3 months, and 6 months post-discharge. PTSS were present in the majority of mothers (55.9%) and fathers (61.5%). PTSS were not associated with illness severity, but were associated with parental report of mood symptoms, avoidance, inflexibility, and symptom accommodation. Parental PTSS may negatively impact the adolescent rate of weight gain post-discharge. As hospitalization of a child for medical management of AN can be a traumatizing experience for parents, astute attention should be paid by medical staff to their needs. More work needs to be done to understand the impact of PTSS on parents of adolescents with AN.